Valorisation of Exhausted Olive Pomace by an Eco-Friendly Solvent Extraction Process of Natural Antioxidants - Irene Gómez-Cruz; Cristóbal Cara; Inmaculada Romero; Eulogio Castro; Beatriz Gullón (MDPI AG, 2020)
Exhausted olive pomace (EOP) is the waste generated from the drying and subsequent extraction of residual oil from the olive pomace. In this work, the effect of different aqueous solvents on the recovery of antioxidant compounds from this lignocellulosic biomass was assessed. Water extraction was selected as the best option for recovering bioactive compounds from EOP, and the influence of the main operational parameters involved in the extraction was evaluated by response surface methodology. Aqueous extraction of EOP under optimised conditions (10% solids, 85 ºC, and 90 min) yielded an extract with concentrations (per g EOP) of phenolic compounds and flavonoids of 44.5 mg gallic acid equivalent and 114.9 mg rutin equivalent, respectively. Hydroxytyrosol was identified as the major phenolic compound in EOP aqueous extracts. Moreover, these extracts showed high antioxidant activity, as well as moderate bactericidal action against some food-borne pathogens. In general, these results indicate the great potential of EOP as a source of bioactive compounds, with potential uses in several industrial applications.